Importance of Knowledge and Literacy about Diabetes Mellitus and Related Factors for Diabetes Patients in the Kahuripan Health Center Working Area, Tasikmalaya City - Anih Kurnia; Betty Suprapti; Teti Agustin; Aruf Nufus; Reni Rahayu; Sifaul Fuadah; Riska Nurmayanti; Deti Widi Astuti (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Diabetes patients require education and expertise in self-care management. A lack of understanding and knowledge about diabetes and diabetes-related topics leads to uncertainty, fear, and skepticism, which are readily exacerbated by emotions. Educating patients about diabetes has been found to improve their clinical results and quality of life. This study aims to identify knowledge and awareness of diabetes self-care management by increasing knowledge through education and demonstration of diabetes self-care management activities in the Kahuripan Community Health Center working area in Tasikmalaya City, to reduce complications. This study used a quantitative descriptive design with total sampling. Activities were conducted to enhance diabetes awareness and literacy. Results. The service participants were 57 persons. D III Nursing Study Program Faculty, with the assistance of students, implemented expanding knowledge in PROLANIS activities. This study used a quantitative descriptive design with total sampling. Activities are carried out to promote knowledge and awareness about diabetes and related issues. Results The service participants were 57 persons. Increased understanding of PROLANIS activities is carried out by D III Nursing Study Program lecturers with the assistance of students. The activity is carried out by preparing and administering the Diabetes Knowledge Questionnaire (DKQ)-24 questionnaire via mobile phone, with the aid of students. The majority of participants, 55 (96.5%), had bad knowledge before the counseling activities and exercise demonstrations. Following the activities, 7 (12.3%) participants had good knowledge, 22 (38.6%) had good knowledge, and 28 (49.1%) participants had poor information. The connection between diabetic self-management behavior and health attitudes is mediated by knowledge and cultural literacy regarding diabetes. Furthermore, because diabetic health literacy can impact patients' ability to manage their treatment, healthcare professionals must evaluate patients' health literacy and create interventions that can raise it. To achieve positive health outcomes, health literacy should be regarded as essential in health education and interactions with emergency services.